Maximizing Ion Permselectivity in MXene/MOF Nanofluidic Membranes for High‐Efficient Blue Energy Generation. (11th October 2022) - Zhou, Jiale; Hao, Junran; Wu, Rong; Su, Liying; Wang, Jie; Qiu, Ming; Bao, Bin; Ning, Chengyun; Teng, Chao; Zhou, Yahong; Jiang, Lei
Abstract: Both ion permeability and selectivity of membranes are crucial for nanofluidic behavior. However, it remains a long‐standing challenge for 2D materials to balance these two factors for osmotic energy harvesting. Herein, the MXene/metal–organic framework (MOF) hybrid membranes are reported to realize efficient ion‐permselective nanofluidic system, leading to high‐performance osmotic power generator. In the system, zeolitic imidazolate framework‐8 (ZIF‐8) is deposited onto the MXene surface and intercalated between the MXene nanosheets by electropolymerization approach. The angstrom‐sized windows of ZIF‐8 layer act as ion selectivity filters, endowing the membrane with high cation selectivity by size effect. The intercalation of ZIF‐8 crystals, reduces the interspacing of MXene, therefore, not only enhancing the ion permeability by shortening the ion transport pathway through the membrane, but also further improving the selectivity by increasing the overlap effect of electric‐double layer. The maximum power density reaches up to 48.05 W m −2 under 500‐fold salinity gradient with a high permeability (1263.3 A m −2 ), and a high selectivity of 0.906 at 50‐fold is obtained. This study provides a facile method to fabricate nanofluidic 2D membranes with both high ion permeability and selectivity for water nexus energy conversion. Abstract : Ti3 C2 Tx MXene/ZIF‐8 hybrid membrane is fabricated by electropolymerization strategy to efficiently harvest osmotic energy. The maximum power density reaches up to 48.05 W m −2 at 500‐fold concentration gradient. The ZIF‐8 layer with angstrom‐scale ion channels endows the membrane with high selectivity (0.906) and further improves the ion permeability (1263.3 A m −2 ) by reducing the interlayer spacing of MXene layer.